Distribution and phylogeny of mercury methylation, demethylation, and reduction genes in the Seto Inland Sea of Japan. (January 2023) - Tada, Yuya; Marumoto, Kohji; Iwamoto, Yoko; Takeda, Kazuhiko; Sakugawa, Hiroshi
Abstract: Mercury (Hg) adversely affects human and environmental health. To evaluate the mercury (Hg) speciation (methylation, demethylation, and reduction) of microorganisms in coastal seawater, we analyzed the microbial functional gene sets involved in Hg methylation ( hgcA and hgcB ), demethylation ( merB ), and reduction ( merA ) using a metagenomic approach in the eastern and western parts (the Kii and Bungo channels, respectively) of the Seto Inland Sea (SIS) of Japan. We determined the concentration of dissolved total mercury (dTHg) and methylated mercury (dMeHg) in seawater. The metagenomic analysis detected hgcAB, merA, and merB in both channels, whereas the phylogenies of these genes differed between them. A correlation between Hg concentration (both dTHg and dMeHg) and the relative abundance of each gene was not observed. Our data suggests that microbial Hg methylation and demethylation could occur in the SIS and there could be a distinct microbial Hg speciation process between the Kii and Bungo channels. Highlights: Mercury-related genes ( hgcAB, merA, and merB ) were detected in the seawaters of the Seto Inland Sea (SIS) of Japan. A correlation between the Hg concentration and the relative abundance of each gene was not observed. Not only microorganisms but also other factors may be important for Hg speciation.